British and Irish emigrants and exiles in Europe, 1603 - 1688 - Worthington, David (The Northern world, 2010)
Community, commodity and commerce: the Stockholm-Scots in the seventeenth century / Steve Murdoch -- Scoti, cives cracovienses: their ethnic and social identity, 1570-1660 / Waldemar Kowalski -- Fortress Rotterdam? Rotterdam's Scots community and the covenanter cause, 1638-1688 / Douglas Catterall -- Special privileges for the Irish in the kingdom of Castile (1601-1680): modern myth or contemporary reality? / Ciaran O'Scea -- Hidden by 1688 and after: Irish Catholic migration to France, 1590-1685 / Éamon Ó Ciosáin -- Murder as a weapon of exile: English politics at the Spanish court (1649-1652) / Igor Pérez Tostado -- Scots in Swedish Bremen and Verden (1645-1712) / Kathrin Zickermann -- The Gordons of Huntly: a Scottish noble household and its European connections, 1603-1688 / Barry Robertson -- "My heart is a Scotch heart": Scottish Calvinist exiles in France in their continental context: 1605-1638 / Siobhan Talbott -- Under the Habsburgs and the Stuarts: the Leslies' Portrait Gallery in Ptuj Castle, Slovenia / Polona Vidmar -- English military émigrés and the Protestant cause in Europe, 1603-c 1640 / David J.B. Trim -- Scottish Catholics abroad, 1603-1688: evidence derived from the archives of the Scots colleges / Tom McInally -- Irish Franciscan networks at home and abroad, 1607-1640 / Thomas O'Connor -- The English convents in exile and questions of national identity, c. 1600-1688 / Caroline Bowden -- Perceptions of the British Isles and Ireland among the Catholic exiles: the case of Robert Corbington SJ / Peter Davidson